Intradermal delivery device and method - Py, Daniel; Chan, Julian V (2005)
The subject intradermal delivery device provides for penetration to a fixed depth without requiring special expertise by the user. The device consists of a syringe nested inside an inner shell and an outer shell. An elongated annular channel is formed between the inner shell and the outer shell. A housing receives the syringe and concentric shells in a sliding engagement. A first seal on the distal end of the housing forms a variable length channel in communication with the elongated annular channel via a port formed in the outer shell. When the device is applied to the skin, the housing and syringe are slid towards the skin, and the variable length channel generates a vacuum which forces the skin to bulge into the elongated annular channel. As a result, the skin is tensioned across the inner shell to form a substantially planar, taut target area of skin. The taut target area of skin in combination with a stop on the housing determines the insertion depth of the syringe.